PENGEMBANGAN MODEL FIDUSIA TERHADAP PENITIPAN BARANG DARI PERSERO PEGADAIAN KEPADA DEBITUR - Muhammad Taufich Hidayat; Martin Roestamy; endeh Suhartini (JURNAL ILMIAH LIVING LAW, 2019)
This study aims: 1) To find out and analyze the development of fiduciary models for safekeeping of goods from PT. Pegadaian to the debtor, 2) To find out and analyze the execution of fiduciary guarantees at PT. Pegadaian if the debtor defaults. The research method used in this study is a normative juridical study that uses a qualitative approach. The results of this study are: 1) Development of the fiduciary model for safekeeping of goods from the PT. Pegadaian to the debtor, namely the Fiduciary Installment Credit System (KREASI), where the credit facility is subject to the provisions applicable to fiduciary law. Debtors who need funds do not hand over objects used as collateral to PT. Pegadaian as a creditor. 2) Execution of fiduciary guarantees at PT. Pegadaian if the debtor defaults, in the execution of fiduciary guarantees at PT. Pegadaian there are differences of opinion between PT. Pegadaian with the State Receivables and Auction Service Office (KP2LN). PT. Pegadaian states that the execution of fiduciary guarantees is carried out on its own with reference to the Basic Rules of PT. Pegadaian. Whereas KP2LN believes that the one authorized to carry out fiduciary guarantees is KP2LN with reference to the Fiduciary Law. In this case the author agrees with KP2LN because the legal basis of the Fiduciary Law is stronger than the Basic Rules of PT. Pegadaian.